Differences in the use of englishism in daily speech in primary school children in relation to sociodemographic variables - Miljković Miljan D. (Institute of Serbian Culture Priština, Leposavić, 2021)
Being surrounded by English language leads us to think that anglicisms are found in everyday language. Innevitably, even children of primary school age come into contact with anglicisms. The online classes that were conducted, and due to the epidemic of the Kovid 19 virus, made the availability of words of foreign origin, in this case from the English-speaking area, even easier. The subject of this paper is to examine the differences in the use of anglicisms among pupils ofthe primary school in Kosovska Mitrovica, aged 9 to 12 years, in relation to sociodemographic variables (gender, grade and age of students, school successand educational level of parents and socioeconomic status of the family). Online survey was conducted offering words of Serbian and English origin with the aim of giving an insight into how many foreign words are used instead of domestic ones. The research found that a statistically significant difference exists only between pupils whose mothers are of different educational levels. Other hypotheses have not been confirmed.